Effectiveness of Sodium Bicarbonate (NaHCO3) on Physicochemical and Sensory Characteristic of Notopterus notopterus Bone Chips - Herpandi Herpandi; Indah Widiastuti; Wulandari Wulandari; Cynthia Aprita Sari (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
This study was aimed to determine the physicochemical and sensory characteristics of chips made from bones of Notopterus notopterus previously soaked in sodium bicarbonate. Different concentrations of sodium bicarbonate (0; 0.5; 1; 1.5; 2; and 2.5%) were used to soak the bones. The parameters observed were chemical analysis, physical analysis, and sensory analysis.  The soaking of  the fish bones in sodium bicarbonate  had significant effects (p<0.05) on the chemical characteristics including water content, ash content, protein content, NaHCO3 residue as well as physical characteristic of the chips. However, on the soaking did not affect phosphorus, calcium and sensory characteristics of the chips.